Emissão de óxido nitroso e metano em área de cultivo com arroz irrigado com diferentes manejos da palha pós-colheita - Souza, Eduardo Lorensi de (2013)
Post-harvest rice straw managements can alter CH4 and N2O emissions and global warming potential (GWP) in lowland areas cultivated with rice. In order to test this hypothesis, the present study was planned to quantify annual N2O and CH4 emissions, GWP and grain yield of rice subjected to different post-harvest straw managements on a lowland area at Southern Brazil. The soil was a Planossol. The treatments were as follows: No management (NM); Post-harvest Roll-knife (RKPH); Post-harvest Disc harrowing (PHDH); Without straw (WS); NM + Ryegrass (NM + RG); Disc harrowing in August (DH); Post-harvest Disc harrowing + Disc harrowing in August (DHPH + DH) and Without straw + Disc harrowing in August (WS + DH). The amount of rice straw returned to the soil in all plots after harvest was adjusted to 6.5 Mg ha-1 in April 2010 and to 11.3 Mg ha-1 in March 2011. Emissions of N2O and CH4 were evaluated for two consecutive years during the periods between harvests and rice cultivation. At each gas sampling time soil samples were also collected to evaluate soil mineral N and moisture contents. GWP of each management system was calculated from soil C contents (at the start of the experiment and at the end of experiment), N2O and CH4 emissions and CO2 cost during all managements. The results showed that more than 98% of the emitted N2O in lowland rice cultivation occurs during fallow period. Nearly whole CH4 emissions were recorded during rice cultivation. Incorporation of rice straw with tillage management after harvest with disc harrowing or growing of ryegrass after harvest lowered N2O emissions during fallow period. The lower CH4 emissions were observed in the treatments where rice straw was incorporated after harvest with disk harrowing and roller knife. These straw management practices also reduced GWP without reducing grain yield, compared to managements that do not incorporate rice straw. Management systems that resemble NT or zero tillage, where straw was left on soil surface during the fallow period resulted in higher N2O and CH4 emissions. Similarly, those management systems where soil was harrowed before planting resulted in soil C loss and contributed towards higher GWP, being less efficient and unsustainable.